PRAKTIK PENGELOLAAN DAN PENJAMINAN HALAL PADA UMKM POTONG AYAM: STUDI KASUS DI WILAYAH ACEH TENGAH - Imeliani, Sandrina Dimas; Malahayatie (International Journal Mathla’ul Anwar of Halal Issues, 2025)
This study aims to examine how halal management and assurance practices are implemented in a micro, small, and medium enterprise (MSME) chicken slaughter business in the Aceh Tengah region, particularly in the context of slaughtering, hygiene, marketing, and the business owner's understanding of the importance of halal certification. Method: This research employed field observation and direct interviews with the MSME owner. Semi-structured interviews were conducted to gather information related to the production process, marketing strategies, and the business owner's level of understanding regarding halal certification. The data were analyzed using a descriptive-qualitative method with a case study approach. Results and Discussion: The findings indicate that the chicken slaughtering process is conducted manually in accordance with Islamic law, supported by the use of a feather-removal machine to make the cleaning process faster and more efficient. Product management remains traditional, from the selection of raw materials, slaughtering process, to simple packaging. Promotion is carried out modestly through social networks and the use of WhatsApp to take orders and communicate with regular customers. The business has not yet obtained official halal certification, and the owner lacks understanding of the procedures and benefits of the certification. The business owner’s awareness of the importance of halal certification remains low, and there is no halal supervisor involved in the production process. This highlights the need for guidance and education to improve MSMEs' understanding of halal product management. Conclusion: This study concludes that although the chicken slaughtering practice complies with basic Islamic principles, formal legal recognition in the form of halal certification has not yet been obtained. This presents a significant challenge for MSMEs in building consumer trust in the growing halal industry. Active involvement from the government, certification bodies, and academics is needed to support MSMEs in enhancing their knowledge, legal compliance, and management of products according to national halal standards.